Physical quality of an Oxisol under an integrated crop-livestock-forest system in the Brazilian Cerrado - Sousa Neto, Eurico Lucas De; Andrioli, Itamar [UNESP]; Almeida, Roberto Giolo De; Macedo, Manuel Cláudio Mota; Lal, Rattan (Sociedade Brasileira de Ciência do Solo, 2014)
Soil physical quality is an important factor for the sustainability of agricultural systems. Thus, the aim of this study was to evaluate soil physical properties and soil organic carbon in a Typic Acrudox under an integrated crop-livestock-forest system. The experiment was carried out in Mato Grosso do Sul, Brazil. Treatments consisted of seven systems: integrated crop-livestock-forest, with 357 trees ha-1 and pasture height of 30 cm (CLF357-30); integrated crop-livestock-forest with 357 trees ha-1 and pasture height of 45 cm (CLF357-45); integrated crop-livestock-forest with 227 trees ha-1 and pasture height of 30 cm (CLF227-30); integrated crop-livestock-forest with 227 trees ha-1 and pasture height of 45 cm (CLF227-45); integrated crop-livestock with pasture height of 30 cm (CL30); integrated crop-livestock with pasture height of 45 cm (CL45) and native vegetation (NV). Soil properties were evaluated for the depths of 0-10 and 10-20 cm. All grazing treatments increased bulk density (r b) and penetration resistance (PR), and decreased total porosity (¦t) and macroporosity (¦ma), compared to NV. The values of r b (1.18-1.47 Mg m-3), ¦ma (0.14-0.17 m³ m-3) and PR (0.62-0.81 MPa) at the 0-10 cm depth were not restrictive to plant growth. The change in land use from NV to CL or CLF decreased soil organic carbon (SOC) and the soil organic carbon pool (SOCpool). All grazing treatments had a similar SOCpool at the 0-10 cm depth and were lower than that for NV (17.58 Mg ha-1).

A qualidade física do solo é um importante fator para a sustentabilidade dos sistemas agrícolas. O objetivo desta pesquisa foi avaliar as propriedades físicas do solo e o carbono orgânico em um Latossolo Vermelho distrófico, sob sistema de integração lavoura-pecuária-floresta. O experimento foi conduzido no Mato Grosso do Sul, Brasil. Os tratamentos consistiram de sete sistemas: integração lavoura-pecuária-floresta, com 357 árvores ha-1 e altura de pastejo de 30 cm (CLF357-30); integração lavoura-pecuária-floresta, com 357 árvores ha-1 e altura do pastejo de 45 cm (CLF357-45); integração lavoura-pecuária-floresta, com 227 árvores ha-1 e altura do pastejo de 30 cm (CLF227-30); integração lavoura-pecuária-floresta, com 227 árvores ha-1 e altura do pastejo de 45 cm (CLF227-45); integração lavoura-pecuária, com a altura do pastejo de 30 cm (CL30); integração lavoura-pecuária, com a altura do pastejo de 45 cm (CL45); e vegetação nativa (NV). As propriedades do solo foram avaliadas nas profundidades de 0-10 e 10-20 cm. Todos os tratamentos com pastagem aumentaram a densidade do solo (r b) e resistência à penetração (RP) e diminuíram a porosidade total (¦t) e macroporosidade (¦ma), em comparação com a NV. Os valores de r b (1,18-1,47 Mg m-3), ¦ma (0,14-0,17 m³ m-3) e PR (0,62-0,81 MPa) na profundidade de 0-10 cm não foram restritivos ao crescimento de plantas. A mudança de uso do solo a partir NV para CL ou CLF diminuiu o carbono orgânico (SOC) e o estoque de carbono orgânico (SOCpool). Todos os tratamentos com pastagem apresentaram SOCpool similar na profundidade de 0-10 cm e foram menores em comparação à NV (17,58 Mg ha-1).
Qualidade física de um Latossolo sob integração lavoura-pecuária-floresta no Cerrado brasileiro
Keywords: Agroforestry; soil organic carbon; Multivariate analysis; Sistema agroflorestal; carbono orgânico; Análise multivariada